2020
DOI: 10.1016/j.jjcc.2019.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Advent of New perioperative care for fluid management after cardiovascular surgery: A review of current evidence

Abstract: weight, and hypoalbuminemia. Although long-term outcome is still unknown, tolvaptan treatment added to conventional diuretics treatment in patients undergoing cardiovascular surgery provides sufficient amount of fluid removal without affecting renal function and serum sodium concentrations, and reduced the incidence of worsening renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
0
12
1
Order By: Relevance
“…One potential bias is the differences in administered medication regimes, especially those affecting hemodynamics (diuretics, 27 , 28 , 29 , 30 inotropes, RAAS antagonists, etc) and therefore, directly or indirectly, impacting RAAS. Among the prescribed contents before surgery, diuretics (7/8 dogs) and amlodipine (6/8 dogs) activate the RAAS, whereas ACEIs (4/8 dogs) and spironolactone (1/8 dogs) suppress the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential bias is the differences in administered medication regimes, especially those affecting hemodynamics (diuretics, 27 , 28 , 29 , 30 inotropes, RAAS antagonists, etc) and therefore, directly or indirectly, impacting RAAS. Among the prescribed contents before surgery, diuretics (7/8 dogs) and amlodipine (6/8 dogs) activate the RAAS, whereas ACEIs (4/8 dogs) and spironolactone (1/8 dogs) suppress the system.…”
Section: Discussionmentioning
confidence: 99%
“…Our data is unique in that RAAS activity was shown to be associated, at least to some extent, with echocardiographic indicators that reflect the severity of the disease. From this perspective, postoperative echocardiographic changes and RAAS might as well be applicable in reverse One potential bias is the differences in administered medication regimes, especially those affecting hemodynamics (diuretics, [27][28][29][30] inotropes, RAAS antagonists, etc) and therefore, directly or indirectly, impacting RAAS. Among the prescribed contents before surgery, diuretics Furthermore, only conventional components of RAAS were considered in this relatively short-term study.…”
Section: Discussionmentioning
confidence: 99%
“…While the effectiveness of TLV for ADHF treatment has been well established, long-term TLV administration for CHF treatment remains controversial. Although several recent studies have demonstrated the usefulness of TLV in patients with CHF, most of them had a small sample size and were observational studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Furthermore, the cost of TLV is much higher than that of other conventional drugs for HF treatment; however, no study has investigated the cost-effectiveness of long-term TLV administration for CHF treatment in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Deep Hypothermic Circulatory Arrest (DHCA) can prolong cardiopulmonary bypass time, cause vascular endothelial dysfunction, and promote in ammatory responses (7)(8)(9). Therefore, su cient volume is required to avert intravascular hypovolemia soon after surgery, due to the persistence of altered vascular permeability and colloidal osmotic pressure (10). The volume is then reduced after stabilization of in ammation and temperature (11).…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been numerous reports indicating the usefulness of tolvaptan in managing postoperative uid volumes in patients with cardiac diseases treated with surgery (10). However, despite the acceptance of tolvaptan for various types of cardiovascular conditions treated by surgery, there is limited information on its use after surgery for type A AD.…”
Section: Introductionmentioning
confidence: 99%